Семен Виноградов - Краснова Вера Владимировна (Удмуртия, 2014)
Экземпляры: Ф. 4 (20190701) / Инвентарный номер: 46317 / Цена: 100.00 / Сис.шифр: 85.143(2Рос.Удм) / Авт.знак: В 49 / ГРНТИ: 18.31.31 / ББК: 85.143(2Рос.Удм)